Українізація міліції УСРР у 1920-ті роки - Греченко, В. А.; Grechenko, V. A.; ORCID: http://orcid.org/0000-0002-6046-0178 (Право і безпека. – 2016. – № 3 (62). – С. 18-22, 2016)
Розглянуто основні аспекти українізації міліції протягом 1920-х років; проаналізовано, як відбувався цей процес, які мав тенденції та особливості.

The main aspects of ukrainization of the police in 1920s have been determined. It has been proved that the policy of ukrainization in the Republic is not held for the first time and has its historical roots. Since 1923 the Soviet Union has started to implement the localization policy as the temporary policy of the Communist Party, which was carried out to strengthen the Soviet power in Ukraine by concessions in the form of implementing Ukrainian language in schools, media, cultural life and in state institutions. According to the decree of the board of the Commissariat of Internal Affairs dated from June 15, 1925 ukrainization of the system had to be completed by January 1, 1926. Minutes of meetings and sessions had to be in Ukrainian, all employees had to do language mastering, and those employees who didn’t know Ukrainian were not recruited for the service. Correspondence with Soviet Republics, organizations and institutions of national minorities and the drafts of resolutions that were submitted to the highest authorities of the Soviet Union remained in Russian. There was an order to fire while personnel reduction primarily employees who didn’t have skills in Ukrainian. Local authorities of People’s Commissariat of Internal Affairs treated differently for the case of ukrainization of its staff; some authorities provided ukrainization only technical clerical staff or even hired translators that led to a distortion of Ukrainian language and often the content of the written text. It has been established that the share of Ukrainians gradually increased among the officers of law enforcement agencies, but this process was slower in Donbas. However, the period of ukrainization was not long, and its conduction was politically and ideologically limited. Coagulation of this process took shape in 1929.

Рассмотрены основные аспекты украинизации милиции в течение 1920-х годов; проанализировано, как происходил этот процесс, какие имел тенденции и особенности.
Ukrainization Of The Police Of Ukrainian Soviet Socialist Republic In 1920s
Украинизация милиции УССР в 1920-ые годы
Греченко, В. А. Українізація міліції УСРР у 1920-ті роки / В. А. Греченко // Право і безпека. – 2016. – № 3 (62). – С. 18-22.
Греченко В. А. "Українізація міліції УСРР у 1920-ті роки." Право і Безпека 3 (2016): 18-22.
Grechenko, V.A. (2016), “Ukrainization of the police of Ukrainian Soviet Socialist Republic in 1920s” [“Ukrainizatsiia militsii USRR u 1920-ti roky”], Pravo i Bezpeka, No. 3, pp. 18–22.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Історія. History. История; Україна. Ukraine. Украина; Наукові публікації. Scientific publications. Научные публикации; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; міліція; милиция; militia; коренізація; українізація; нова економічна політика; localization policy; ukrainization; new economic policy; коренизация; украинизация; новая экономическая политика